Peningkatan Hasil Belajar Tematik Menggunakan Strategi Pembelajaran Think-Tac-Toe pada Siswa Tunagrahita Ringan - Nabilla, Ihsa; Iswari, Mega; Evanofrita, Evanofrita (Jurnal Penelitian Pendidikan Khusus, 2023)
Students with mild intellectual disabilities experience problems related to academic abilities because their intelligence level is below average at an IQ of 50-70. As a result, student learning outcomes in class are low. However, academic potential can still be developed optimally. The aim of this research is to improve thematic learning outcomes using the think-tac-toe strategy for students in class VII C class VII C light class 4 Tunagrhaita at SLB YPPLB Padang. Research was carried out on theme 5 (ecosystem), sub-theme 2 (ecosystem components), learning 3 (relationship of biotic and abiotic components) with content in Indonesian, science and mathematics. The low student learning outcomes were due to the strategies used previously being conventional and not accommodating student needs. The research method used is Collaborative PTK in 2 cycles, with stages of planning, implementation, observation and reflection. Data was obtained using observation, tests and interviews. Data analysis uses quantitative analysis in the form of visual graphs and qualitative analysis in the form of information in learning. The research results showed that there was an increase in thematic learning outcomes for blind students using the Think-tac-toe strategy.